Comparison of Education Policy USA & Indonesia - Ulul Albab (International Journal of Social Service and Research, 2022)
In public policy, both from Feldman's and Heidenheimer's definitions of CPP (Comparative Public Policy), we can conclude that there are 3 elements (elements) that are keywords that are the center of attention of CPP. In Feldman's terms, the 3 keywords are "process," "output," and "outcomes," while the keywords used by Heidenheimer are "haw," "why," and "to what effect." There are at least 3 reasons and objectives for comparing existing public policies between certain countries and other countries, or between existing policies in our country and policies in other countries. Namely: To get an overview and lessons on how to design a good policy. To gain a more profound and better understanding of how the role of government institutions and political processes (as they should be) is primarily related to the formulation and resolution of concrete problems that develop in society. To review various existing policies across the national level. Qualitative analysis method using SWOT. This is based on a qualitative study, not a quantitative one. This analysis refers to the results of studies and references on the existing Decentralization of education, including relevant books and publications. The comparison of public policies results includes Choices of Scope, Choices of Policy Instruments, Choices of Distribution, Choices of Restraints, and Innovation. In the United States, the education decentralization policy has proven to be an option to make it easier for the Government to deal with problems in detail and create alternative options for further improvement of education policy with innovations that vary from district to district. In Indonesia, the education decentralization policy has been able to help the central Government more quickly and in detail solve problems that arise in the education sector